2008
DOI: 10.1074/jbc.m803517200
|View full text |Cite
|
Sign up to set email alerts
|

Control of Translocation through the Sec61 Translocon by Nascent Polypeptide Structure within the Ribosome

Abstract: During polytopic protein biogenesis, multiple transmembrane segments (TMs) must pass through the ribosome exit tunnel and into the Sec61 translocon prior to insertion into the endoplasmic reticulum membrane. To investigate how movement of a newly synthesized TM along this integration pathway might be influenced by synthesis of a second TM, we used photocross-linking probes to detect the proximity of ribosomebound nascent polypeptides to Sec61␣. Probes were inserted at sequential sites within TM2 of the aquapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 60 publications
0
29
1
Order By: Relevance
“…It is attractive to speculate that in vivo a preference of SRP for its prime substrates is facilitated by recruitment to RNCs translating hydrophobic SAs even before these emerge at the tunnel exit. Although the mechanism is not understood, it may resemble ribosomal recognition of a nascent transmembrane domain that was found to affect the operational mode of the ribosome-bound translocon in the ER membrane (30,35,36). Consistent with such a model, it is the hydrophobicity of a signal sequence that determines whether or not a protein enters the coor posttranslational pathway in vivo (16).…”
Section: Discussionmentioning
confidence: 86%
“…It is attractive to speculate that in vivo a preference of SRP for its prime substrates is facilitated by recruitment to RNCs translating hydrophobic SAs even before these emerge at the tunnel exit. Although the mechanism is not understood, it may resemble ribosomal recognition of a nascent transmembrane domain that was found to affect the operational mode of the ribosome-bound translocon in the ER membrane (30,35,36). Consistent with such a model, it is the hydrophobicity of a signal sequence that determines whether or not a protein enters the coor posttranslational pathway in vivo (16).…”
Section: Discussionmentioning
confidence: 86%
“…S4). Although crosslinking using BMH, or other such reagents, can never achieve complete efficiency, the synchronisation of stalled nascent chains and the analysis of only C-terminally tagged polypeptides ensures that this approach accurately reports the environment of the bulk of the P2X2 chains present in each reaction (see also Daniel et al, 2008;Ismail et al, 2006;Mothes et al, 1997;Pitonzo et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Assignment of topology is partially determined by electrostatic interaction between charged residues flanking the signal core and charged residues located at the plug and the C-terminal end of TM8 in the channel; these residues are likely to contribute to an electrostatic clamp. The study of the Sec61-mediated biogenesis of aquaporin-4, an all α-helical integral polytopic protein (37,38), showed that each TM interacted with and moved through Sec61α in a highly ordered and sequential manner and suggested the presence of a single primary binding site. Our structure may reveal the modality of such interactions at this primary binding site.…”
Section: General Model For the Priming Of The Translocon For Protein mentioning
confidence: 99%